Design and construction of the mined Kısıklı Station on the Üsküdar‐Çekmeköy Metro Line Project. Issue 4 (August 2016) - Özcan, Barış; Duman, Emre; Türkoǧlu, Aykut; Kayalı, Sanem; Saenz, Ignacio
Abstract: The Üsküdar‐Çekmeköy Metro Line (UCM), which is located on the Asian side of Istanbul, is an 18 km underground metro line with 27 km of TBM tunnel, 13 km of NATM tunnel and 16 stations. Apart from being a completely tunnelled station, it has several other features. It is the deepest station in this metro line with the platform depth 45 m below surface level. The station is being built in a complex geology that contains several passive fault zones. The ticket hall and technical rooms are also located in an NATM tunnel with an excavated width of 20 m. Most of the passenger circulation is planned to be carried out by elevators. The station has been designed with two levels of NATM tunnels with four main elliptical shafts. The geology varies from very strong quartz arenite with a compressive strength of 77 MPa to highly weathered fault zones containing andesite. The complex geometry and geology of the station dictated utmost care for excavation and final lining design of the NATM sections in order to provide stability during excavation and sufficient structural capacity in case of a seismic event.